The Great Pretender: the lichen Peltigera provides a leaf-like habitat for Iceland's unique genetic lines of Pseudomonas syringae. - Ramirez, Natalia; Sigurbjörnsdóttir, Margrét Audur; Berge, Odile; Vilhelmsson, Oddur; Morris, Cindy E. (HAL CCSD, 2022)
International audience Plants in Iceland harbor unique genetic lineages of the Pseudomonas syringae complex (Ps) that emerged on the island several MYA. We are now investigating the capacity of lichens to harbor these Ps. Lichens are represented by >700 spp and colonize a wider range of habitats than plants occupy in Iceland. They harbor a rich bacterial flora dominated by Alphaproteobacteria but the presence of Ps is currently unknown. We screened 16 lichen spp and found Ps on all samples of the leaf-like Peltigera spp but not on other genera. Mean population densities of Ps on Peltigera spp were ca. 200 bacteria/g whereas they were about 10x greater on adjacent angiosperms and mosses in spite of similar densities of total cultural bacteria. Strains from Ps phylogroup (PG) 10 dominated most lichen populations, but strains in PG01 and/or PG02 were detected on half of the samples. Their phytopathogenic capacity is being assessed.